(untitled) (Psicologia USP, 1992)
This paper reports the contribution of kinship studies to the understanding of the family. It refers to the anthropological contribution to the subject, particularly on the analysis of the social character of the family and the non-universality of our pattern of nuclear family. It also highlights the meaning of marriage and the incest taboo as social institutions, stressed mainly by the work of Lévi-Strauss, a turning point in anthropological thought on kinship. The decomposition of the different relations that compose kinship and the family presented in the text, helps one to understand their social character and that family change is not a totalizing process.